Early diet of preterm infants and development of allergic or atopic disease: randomised prospective study. Issue 6728 (31st March 1990) - Lucas, A; Brooke, O G; Morley, R; Cole, T J; Bamford, M F
Abstract : OBJECTIVE–To study the effect of early diet on the development of allergic reactions in infants born preterm. DESIGN–Two randomised prospective trails. In trail A infants were randomly allocated banked donor milk or preterm formula as their sole diet or (separately randomised) as a supplement to their mother's expressed breast milk. In trial B infants were allocated term or preterm formula. A blind follow up examination was done 18 months after the expected date of birth. SETTING–Neonatal units of hospitals in Cambridge, Ipswich, King's Lynn, Norwich, and Sheffield. Outpatient follow up. PARTICIPANTS–777 Infants with a birth weight less than 1850 g born during 1982 to 1984. MAIN OUTCOME MEASURES–Development of eczema, allergic reactions to food or drugs, and asthma or wheezing by nine and 18 months after term. Whenever possible the observations were confirmed by rechallenge or clinical examination. RESULTS–At 18 months after term there was no difference in the incidence of allergic reactions between dietary groups in either trial. In the subgroup of infants with a family history of atopy, however, those in trial A who received preterm formula rather than human milk had a significantly greater risk of developing one or more allergic reactions (notably eczema) by 18 months (odds ratio 3.6; 95% confidence interval 1.4 to 9.1). CONCLUSIONS–Feeding neonates on formulas based on cows' milk, including those with a high protein content, did not increase the overall risk of allergy. Nevertheless, in the subgroup with a family history of atopy early exposure to cows' milk increased the risk of a wide range of allergic reactions, especially eczema.